Repair of O(4)-Alkylthymine by O(6)-Alkylguanine-DNA Alkyltransferases - Fang, Qingming (American Society for Biochemistry and Molecular Biology, 2010)
O(6)-Alkylguanine-DNA alkyltransferase (AGT) plays a major role in repair of the cytotoxic and mutagenic lesion O(6)-methylguanine (m(6)G) in DNA. Unlike the Escherichia coli alkyltransferase Ogt that also repairs O(4)-methylthymine (m(4)T) efficiently, the human AGT (hAGT) acts poorly on m(4)T. Here we made several hAGT mutants in which residues near the cysteine acceptor site were replaced by corresponding residues from Ogt to investigate the basis for the inefficiency of hAGT in repair of m(4)T. Construct hAGT-03 (where hAGT sequence -V(149)CSSGAVGN(157)- was replaced with the corresponding Ogt -I(143)GRNGTMTG(151)-) exhibited enhanced m(4)T repair activity in vitro compared with hAGT. Three AGT proteins (hAGT, hAGT-03, and Ogt) exhibited similar protection from killing by N-methyl-N′-nitro-N-nitrosoguanidine and caused a reduction in m(6)G-induced G:C to A:T mutations in both nucleotide excision repair (NER)-proficient and -deficient Escherichia coli strains that lack endogenous AGTs. hAGT-03 resembled Ogt in totally reducing the m(4)T-induced T:A to C:G mutations in NER-proficient and -deficient strains. Surprisingly, wild type hAGT expression caused a significant but incomplete decrease in NER-deficient strains but a slight increase in T:A to C:G mutation frequency in NER-proficient strains. The T:A to C:G mutations due to O(4)-alkylthymine formed by ethylating and propylating agents were also efficiently reduced by either hAGT-03 or Ogt, whereas hAGT had little effect irrespective of NER status. These results show that specific alterations in the hAGT active site facilitate efficient recognition and repair of O(4)-alkylthymines and reveal damage-dependent interactions of base and nucleotide excision repair.